2004
DOI: 10.5713/ajas.2004.1107
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Rumen Degradability of Some Legume Forages between Wet and Dry Season in West Sumatra, Indonesia

Abstract: An experiment was conducted to evaluate the potential nutritive value of five legume forages (leaves and twigs) in West Sumatra during wet and dry seasons. The chemical composition, in vitro dry matter (IVDMD), organic matter (IVOMD) and crude protein digestibility (IVCPD), in vitro gas characteristics and estimated metabolizable energy (ME) showed variation among legume forages and between different seasons. Crude protein (CP) ranged from 14.2 to 27.8% DM in the wet season, with a significant (p<0.05) reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
7
10
1
5
Order By: Relevance
“…Such seasonal changes in the chemical compositions of grasses in tropical climates are a result of the maturity and age of the grass species with the progression of seasons from the dry to rainy season. The lower CP content in the dry season was in agreement with the results reported by Aregheore (2002) and Evitayani et al . (2004a).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Such seasonal changes in the chemical compositions of grasses in tropical climates are a result of the maturity and age of the grass species with the progression of seasons from the dry to rainy season. The lower CP content in the dry season was in agreement with the results reported by Aregheore (2002) and Evitayani et al . (2004a).…”
Section: Resultssupporting
confidence: 93%
“…In both of the seasons, the highest ME content was prominent for P. purpureum and C. plectostachyus . The ME content of grasses in the present study was relatively higher than the ME content of several legumes in North Sumatra, varying from 6.4 to 7.8 MJ/kg in the dry season and from 6.9 to 7.8 MJ/kg in the wet season (Evitayani et al . 2004a).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…In the current study, large differences in the nutritive value of Acacia leaves (as assessed by gas production and DM degradability) were observed, which were primarily the result of changes in maturity. Reduction (P<0.01) in the CP content of ASL in summer versus other seasons, is consistent with other studies, as was the observation that the minimum CP content of fodder tree leaves in the dry season was more than twice that of grasses in the wet season (Skarpe and Bergstrom, 1986;Evitayani et al, 2004). However, the CP content of ASL remained relatively high (143 g/kg DM) in the dry season, suggesting the possibility that Acacia sp.…”
Section: Chemical Compositionsupporting
confidence: 91%
“…Our observations are similar to Evitayani et al (2004), who found that IVGP and IVDMD of some legume species increased in the wet season (winter) compared with the dry season (summer). The effect of season on gas production for cattle and sheep, and in DM degradability for all species could be due to effects of CT on available N in leaves which, in summer, had a highly negative effect resulting in low rumen ammonia concentrations (Bonsi et al, 1995), which then reduced microbial growth.…”
Section: In Vitro Gas Production and Dry Matter Degradabilitysupporting
confidence: 91%